2019
DOI: 10.31557/apjcp.2019.20.2.503
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thymidylate Synthase (TS) and Dihydropyrimidine Dehydrogenase (DPD) Expressions on 5-Fluorouracil in Oral Squamous Cell Carcinoma

Abstract: Background:The study aims to analyze Thymidylate Synthase (TS) and Dihydropyrimidine Dehydrogenase (DPD) Expressions on 5-Fluorouracil in Oral Squamous Cell Carcinoma (OSCC). Methods:50 oral squamous cell carcinoma samples were taken from non-treated cancer patients at Hiroshima University Dental Hospital. The patients were investigated for TS, that included 36 males and 14 females. Additionally, 31 patients were evaluated for DPD that included 22 males and 9 females.Results:The samples had also undergone clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Also, the inhibition of tumoral dihydropyrimidine dehydrogenase increased the sensitivity threshold of cancer cells to this medication. 29 Gao et al 30 evaluated mRNA expression by the cancer cells in 399 patients with HNSCC and showed that high expression of interleukin 6 was associated with poor prognosis and chemical resistance in many cancer cells, without requiring any mediator.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the inhibition of tumoral dihydropyrimidine dehydrogenase increased the sensitivity threshold of cancer cells to this medication. 29 Gao et al 30 evaluated mRNA expression by the cancer cells in 399 patients with HNSCC and showed that high expression of interleukin 6 was associated with poor prognosis and chemical resistance in many cancer cells, without requiring any mediator.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial methylenetetrahydrofolate dehydrogenase 2 and its downstream purine synthesis pathway played an important role in the chemoresistance of lung cancer cells to gefitinib [94]. Akhter et al reported that over-expression of intratumoral thymidylate synthase significantly contributed to the resistance while suppression of dihydropyrimidine dehydrogenase enhanced the sensitivity of 5-FU treatment in oral squamous cell carcinoma [95]. Nicotinamide phosphoribosyltransferase (NAMPT) is an important enzyme for tumor nicotinamide metabolism, which catalyzes the biosynthesis of nicotinamide adenine dinucleotide.…”
Section: Nucleotide Metabolismmentioning
confidence: 99%
“…Various Phase III trials observed that participants with nonsquamous NSCLC had better response rates with pemetrexed compared to those with other histologic subtypes (36)(37)(38). Such an observation has been explained by the presence of thymidylate synthase (TS) which is expressed in SCC (39). However, the mechanism by which the expression of TS influences response to pemetrexed is not yet well understood.…”
Section: Introduction Of New Treatments Based On Histological Charact...mentioning
confidence: 99%